PENGATURAN “TANAH SOKO” PADA MASYARAKAT DESA GANTING KECAMATAN SALO KABUPATEN KAMPAR - Marsella, Triana Anjesti; ', Yesi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted in Ganting Village, Salo District, Kampar Regency with the aim of: 1) Knowing how the Tanah Soko property rights are regulated and 2) How women view the Tanah Soko property rights arrangement. This research was conducted using descriptive qualitative methods with data collection techniques in the form of in-depth interviews, observation and documentation. The subjects of this study were selected as many as 3 main informants, namely indigenous women who became heirs of Tanah Soko and 3 key informants, namely Kampar historians and cultural observers, village officials, and Ninik Mamak. The data analysis technique in this study was carried out through a data re duction process, presentation of data, and drawing conclusions. The theory used in this research is from Talcot Parsons, namely the AGIL theory (Adaptation, Goal, Integration, and Latency). The results of the research show that in the Kampar community's inheritance system, especially the Ganting Village community, adheres to a matrilineal system, namely an inheritance system based on the mother's lineage. Tanah Soko is a form of Tanah Ulayat whose inheritance is given only to women from generation to generation, and may not be sold. Tanah Soko is also called tribal land. The arrangement of Tanah Soko ownership rights in the Ganting Village community can be seen from the existence of statutory and customary arrangements. Keywords : Tanah Soko, Society, Kampar